TINJAUAN YURIDIS TERHADAP PENYELESAIAN SENGKETA PECEMARAN LINGKUNGAN HIDUP DILUAR PENGADILAN, TERKAIT PERAN DAN FUNGSI PEMERINTAH DALAM PENGELOLAAN LINGKUNGAN HIDUP - JOKO SIDIK FITRAYONO (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
AbstractThe province of East Kalimantan, especially the city of Samarinda has a lot of abundant natural resources potential, so the development of this city depends on the exploitation of natural resources, although every year the government seeks to change the consumptive behavior of regional development, from the use and exploitation of natural resource exploitation to become the center of service industry and tourism area, so that Samarinda City does not depend on the exploitation of natural resources Sub Sector of Coal Mining in the original revenue area for regional development.Environment Department of Samarinda City to be more active in constructing constructive communication to the Samarinda City Community, through making public complaint post, socialization to the community, and providing information about the living environment adequate, because in performing its duties and functions Environment Department of Samarinda City is in desperate need community participation so that the community plays an active role in environmental management.